MANAGEMENT OF RELIGIOUS CHARACTER FORMATION OF STUDENTS AT MADRASAH TSANAWIYAH NEGERI 3 BANJARMASIN CITY - Sarkati; M. Fadilah; Mahmudah (Indonesian Journal of Education (INJOE), 2022)
The decline in adolescent moral values is a sign that character education has not gone as expected. Religious character education is very important. In order for the formation of religious character to be carried out optimally, a good management process is needed. This study aims to determine the management of the formation of religious character students at Madrasah Tsanawiyah Negeri 3 Banjarmasin City and its supporting and inhibiting factors. This type field research with a qualitative approach. Data collection techniques with observation, interviews, and documentation. The results of the study show that the management of the formation of religious character students is carried out through: planning, setting goals based on the vision and mission and preparing program plans. Organizing, madrasahs headmaster divides tasks among the wakamad of student affairs, homeroom teachers and educators. Implementation, instilling religious aspects through application to learning, madrasah culture (exemplary, habituation, spontaneous), as well as self-development programs (memorization of juz 30 and selected surahs, applicable fiqh, Friday taqwa, tadarus, PHBI). Supervision is carried out continuously by giving advice, punishment and points. Supporting factors: a conducive madrasah environment, exemplary educators, and parental motivation. Inhibiting factors: bad habits of students, bad association, inadequate facilities, and influence of gadgets.